2020
DOI: 10.1109/jlt.2020.2971273
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and Optimum Signal Constellations for VLC Systems

Abstract: In this paper, the capacity of the point-to-point VLC system is investigated by means of functional analysis subject to amplitude constraint (and average intensity constraint). It is proved that the capacity can be reached by a unique probability density function (PDF). Two sets of necessary and sufficient conditions for the optimum PDF are derived. Moreover, the capacity-achieving PDF are proved to be discrete and finite. Given that the capacity can be achieved by a set of discrete and finite constellations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Proof 8: See Appendix H. 5 Similar to the lower bound in Theorem 2, the lower bound in Theorem 6 is also valid for all values of optical intensities. 6 Similar to the upper bound in Theorem 3, the upper bound in Theorem 7 is also valid only when the optical intensity is sufficiently large.…”
Section: B Capacity Upper Boundmentioning
confidence: 80%
See 3 more Smart Citations
“…Proof 8: See Appendix H. 5 Similar to the lower bound in Theorem 2, the lower bound in Theorem 6 is also valid for all values of optical intensities. 6 Similar to the upper bound in Theorem 3, the upper bound in Theorem 7 is also valid only when the optical intensity is sufficiently large.…”
Section: B Capacity Upper Boundmentioning
confidence: 80%
“…Remark 1. For the VLC having only the signal-independent noise, we derive the secrecy capacity lower bound (15) in Corollary 1 based on the principle of OELIE (11), while the authors in [29] also derived a lower bound ( 8) by using the entropy power inequality (EPI). It can be easily shown that the lower bound (15) in Corollary 1 is smaller than the lower bound (8) in [29].…”
Section: A Lower Bound On Secrecy Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Visible light communication (VLC) is a promising technique for indoor short-range wireless communications systems [1,2]. It has many advantages such as high anti-electromagnetic interference, low cost, good safety, and a rich and license-free spectrum.…”
Section: Introductionmentioning
confidence: 99%